Final Report of a Novel and Successful Online Public Health Capacity Building Experiment – Peoples-uni - Richard Frederick Heller; Alan Barrett; Omo Oaiya; Jane Heller; Rajan Madhok (Open Praxis, 2022)
The People’s Open Access Education Initiative (Peoples-uni) was established as an educational charity to help reduce inequalities in access to the higher education required to build Public Health capacity through workforce development for health professionals in low- to middle-income countries (LMICs). Online learning, using open source software, Open Educational Resources and an international cadre of volunteer tutors, underpinned a low cost programme which produced a number of successful outcomes including university validated master’s level awards, continuing professional development, positive feedback from students, and the application by alumni of skills learned. Peoples-uni closed in 2021, its programme taken over by another organisation, and this paper builds on previous reports to summarise the experience and draw lessons for others who may wish to contribute in a similar way.